1973
DOI: 10.1042/bj1350361
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of deuteroferrihaem by hydrogen peroxide

Abstract: 1. The oxidation of deuteroferrihaem by H(2)O(2) to bile pigment and CO was studied both by stopped-flow kinetic spectrophotometry and mass spectrometry, at 25 degrees C, I=0.1m. 2. Spectrophotometric studies imply that, at constant pH, the rate of bile pigment formation is first-order with respect to [H(2)O(2)] and also proportional to [deuteroferrihaem monomer]. The effect of pH on the apparent second-order rate constant suggests that acid-ionization of deuteroferrihaem monomer is important in the reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 9 publications
1
17
1
Order By: Relevance
“…These spectral changes are characteristic of ferrihemes interacting with hydrogen peroxide (Jones, Prudhoe and Robson, 1973;Jones et al, 1974;Kelly et al, 1977) and agree with earlier reports for microperoxidases 8 and 11 (Clore et al, 1981;Cunningham and Snare, 1992). These observations are also similar to results reported for the classical peroxidase, horseradish (HRP) (Dunford, 1991).…”
Section: Interaction Of Mp11 With H 2 Osupporting
confidence: 91%
See 1 more Smart Citation
“…These spectral changes are characteristic of ferrihemes interacting with hydrogen peroxide (Jones, Prudhoe and Robson, 1973;Jones et al, 1974;Kelly et al, 1977) and agree with earlier reports for microperoxidases 8 and 11 (Clore et al, 1981;Cunningham and Snare, 1992). These observations are also similar to results reported for the classical peroxidase, horseradish (HRP) (Dunford, 1991).…”
Section: Interaction Of Mp11 With H 2 Osupporting
confidence: 91%
“…By analogy to HRP, the observed spectral changes can be attributed to the formation of a peroxidatic intermediate of MP11, an analog of peroxidase compound I. The peroxidase compound I is formed via a heterolytic cleavage of HO-OH in the peroxidase/ H 2 O 2 complex, and contains a high valent iron-oxo ferryl moiety (Fe IV 5 5O) and a p-radical cation localized on the protoporphyrin ring (Jones et al, 1973(Jones et al, , 1974Kelly et al, 1977;Dunford, 1991;Cunningham and Snare, 1992). A similar structure can be envisaged for the reactive intermediate from MP11.…”
Section: Interaction Of Mp11 With H 2 Omentioning
confidence: 94%
“…This also explains the observed decrease in the rate of the reaction of H 2 O 2 with wild-type Mb after mutation, as the mutation removes the residue involved in facilitating the formation of Fe-OOH. An increase in the rate of formation of the peroxide with an increase in pH has also been reported for protoferriheme and deuteroferriheme (Brown and Jones, 1968;Jones et al, 1973), which indicates that [Gly64]Mb behaves like an isolated heme in its reaction with hydroperoxide.…”
Section: Discussionmentioning
confidence: 85%
“…This paper describes the complete structural elucidation of this product as an iron hydroxychlorin compound with saturation of ring D and reports the kinetics of the compound's formation and subsequent hydrolysis to form a corresponding diol. Although oxidation of the heme at the meso position has been proposed to occur during peroxidemediated alteration of metmyoglobin (11), cytochrome P450 (29), ferric heme (29,30), and model ferric hemes (31), we found in the current study that iron hydroxychlorins are formed.…”
mentioning
confidence: 65%
“…This was unexpected as the initial oxidation of the meso carbon has been proposed to account for the peroxidedependent degradation of the heme of myoglobin (11), heme of cytochrome P450 (29), as well as heme (29,30) and model hemes (29,31) in solution. Furthermore, the peroxidemediated reaction is thought to mimic, in part, the initial oxidation of the meso carbon that occurs in the physiological heme degradation reaction catalyzed by heme oxygenase as well as in the coupled oxidation reaction of heme and hemoproteins (30,31,40). More recently, it has been shown that peroxide alone can support the heme oxygenase reaction to give verdoheme, strongly suggesting that a ferric iron-bound 94 (1997)peroxide complex is responsible for meso-hydroxylation (41).…”
Section: Discussionmentioning
confidence: 99%